HUBUNGAN PENGETAHUAN WANITA USIA SUBUR DENGAN PERILAKU PEMERIKSAAN PAYUDARA SENDIRI DI PUSKESMAS KOTAGEDE 1 KOTA YOGYAKARTA - Hasnita, Reni; Ningsih, Sri Ratna (Midwifery Journal: Jurnal Kebidanan UM. Mataram, 2024)
Abstract: Breast cancer is a life threatening disease in the world and in Indonesia. Efforts can be made to detect breast cancer as early as possible by conducting breast self-examination (BSE). This study aimsto determine the relationship between knowledge of women of childbearing age with breast self-examination (BSE) behaviour at Kotagede 1 Primary Health Center. The sampling technique used was puposive sampling technique with a sample 69 women of childbearing age. The measuring instrument used a knowledge questionnaire and SADARI behavior, and statistical analysis using Spearman Rhank. The results showed that most of them had sufficient knowledge, namely 40.6% and poor SADARI behavior, namely 53.6%. the result of bivariate analysis showed that there was a relationship between knowledge of women of childbearing age with breast self-examination (BSE) behaviour with (p-value = 0.000) with strong correlation strength (0.733). there is a correlation between knowledge of women of childbearing age with breast self-examination (BSE) behaviour at Kotagede 1 Primary Health Center in Yogyakarta. Respondents are expected to enhance their understanding of BSE and breast cancer, hence cultivating the necessary awareness to angage in frecuent BSE practises for the ealy detection of breast cancer. health workers who have more authority in carrying out management.Abstrak: Kanker payudara menjadi penyakit yang mengancam kehidupan di dunia maupun di Indonesia. Upaya yang dapat dilakukan untuk mendeteksi sedini mungkin kanker payudara dengan melakukan pemeriksaan payudara sendiri (SADARI). Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan wanita usia subur dengan perilaku pemeriksaan payudara sendiri (SADARI) Di Puskesmas Kotagede 1. Teknik pengambilan sampel yang digunakan yaitu Purposive Sampling dengan sampel 69 wanita usia subur. Alat ukur menggunakan kuesioner pengetahuan dan perilaku SADARI, serta analisis statistik menggunakan Spearman Rhank. Hasil penelitian menunjukkan sebagian besar memiliki pengetahuan cukup yaitu 40.6% dan perilaku SADARI kurang yaitu 53.6%. Hasil analisis bivariate didapatkan ada hubungan pengetahuan wanita usia subur dengan perilaku pemeriksaan payudara sendiri (SADARI) dengan (p-value = 0.000) dengan kekuatan korelasi kuat (0.733). Ada hubungan pengetahuan wanita usia subur dengan perilaku pemeriksaan payudara sendiri (SADARI) di Puskesmas Kotagede 1 Kota Yogyakarta. Diharapkan responden untuk memperluas pengetahuan tentang SADARI dan kanker payudara agar dapat memiliki kesadaran untuk melakukan SADARI secara rutin untuk mendeteksi secara dini kanker payudara.